Evaluation of the New City of Sahand Using the Urban Carrying Capacity Assessment System - Firooz Jafari; Akbar Asghari Zamani; Shiva Sattarzadeh Salehi (برنامه ریزی فضایی, 2022)
AbstractAmong the main challenges in big cities, especially megacities, is the excessive increase in population regardless of the capacity of services and facilities to meet the basic needs of citizens. Identifying the factors affecting biological sustainability, measuring population capacity, and providing management strategies to improve the city were among the goals of this research. The information needed for the research was prepared via document-library and field methods. The fuzzy method was used to descale the indicators of population, water, electricity, and green space. Then, the mentioned indicators were used in the ArcGIS software environment with the methods of Gates Ardeji statistics, Moran's spatial autocorrelation analysis, Morris technique zoning, together with the model. After analyzing the pressure number, the results showed that the Moran values of population, water, electricity, and green space were 0.17, 0.15, 0.15, and 0.03, respectively. Therefore, the first three indicators followed a strong cluster pattern, while the green space index was scattered and distributed in the surface of the city. The maximum capacity of the population, carrying capacity of water, electricity, and green space indicators were equal to 105639, 129121, and 528540 people, respectively. Based on the analysis of population tolerance threshold, water consumption, and electricity distribution, the new city of Sahand was in the critical pressure range, while the green space index was at the optimal threshold so that in the last several years, the city had had a very good green space per capita. Its bearing capacity was more than 80%. IntroductionWith the growth of urbanization and urbanism, the problems of the urban environment have reached a critical level, while one of the most important issues in the today’s world is the problem of preserving the environment. To achieve sustainable urban development, it is necessary to establish appropriate laws and regulations and correctly implement them, as well as changing consumption patterns and environmental attitudes. The purpose of creating new cities can be attraction of the population overflow of cities, reduction of the economic activities of the mother city, regional development, and the use of natural resources, as well as optimal distribution of the population. In fact, these cities are created to help solve the economic, social, and environmental problems of big cities. Therefore, creation of new cities is a response to "megalopolis" or excessive concentration of population and economic activities in big cities. The new city of Sahand (Tabriz) is an example of these new cities, which has been created to attract the overflowing population of Tabriz metropolis with a high population density compared to other areas. The purpose of this research was to evaluate the urban range capacity system in the new city of Sahand by relying on the indicators of population, water, electricity, and green space and trying to estimate the population capacity of the city from an environmental point of view and the amount of pressure on it besides determining which indicator can be applied in its planning. Materials & MethodsThe information required for the research was collected by directly referring to the city institutions, such as New Sahand City Municipality, New Sahand City Development Company, New City Water and Sewerage Department, East Azerbaijan Power Distribution Company, etc., as well as studying documents and electronic library resources, and conducting field studies. The statistical population of the present study included the citizens of the new city of Sahand. Due to the fact that the statistical blocks were not ready to be obtained in 2022 from the data of the previous years (2012-2017), the population of the city in 2022 was fulfilled. The urban range capacity indicators studied in this research were population (population in 2017 and 2022), water (production and annual water consumption of the new city of Sahand in 2022 in cubic meters), electricity (total number of subscribers in domestic, public, agricultural, and industrial sectors and other users, road lighting (based on people and energy consumption in 2022), and green space (areas of parks and green spaces based on each phase and number of the existing parks). These 4 indicators (population, water, electricity, and green space) were first descaled by the fuzzy method and then, the hot-cold spot method and Moran's spatial autocorrelation were used to analyze the spatial distribution of the urban range capacity system in the Arc GIS 10.8.1 software environment. The indicators used were measured and a consolidated index was obtained by using the Morris zoning technique. Finally, it was determined which phases of the new city of Sahand had services and facilities and which ones lacked them. Research findingsAccording to the general and housing population census of 2015, the new city of Sahand had a population of 82494, while the city of Tabriz as the mother city had a population of 1,558,693. The increase in the price of housing in the city of Tabriz and appropriateness of its price in the new city of Sahand, compared to the metropolitan city of Tabriz, especially for the low and middle-income classes, as well as the policy of building Mehr housing in the new city of Sahand had greatly increased the population of the studied city so that the population growth rate of the studied city had reached from 12.66% during the years of 2007-2012 to more than 27.27% during the years 2012-2017. This rate had also increased greatly during the last 5 years according to the estimates. The population of the new city of Sahand in 2022 had reached more than 275000 people. It should be noted that out of the total of 5 phases designed for this city, Phase 5 had not yet been used and was empty. Thus, the mentioned phase was defined as zero in the calculations and only Phases 1, 2, 3, and 4 of the new city of Sahand were analyzed in the analysis of hot and cold spots. Discussion of Results & ConclusionToday, the dominant view in the field of sustainability of cities is that they should be able to provide a good quality of living for their citizens and be receptive to the population as much as possible. Excessive density of population in urban environments is one of the most important factors in creating environmental problems in cities. In this research, according to the standards defined based on the indicators of population, water, electricity, and green space, evaluation of the urban range capacity system in the new city of Sahand was done by using the method of hot-cold spots and spatial autocorrelation analysis. Moran’s spatial autocorrelation analysis was used to determine the spatial distributions of the mentioned indicators for the existing 4 phases of the new city of Sahand. The results showed that the Moran’s values for the indices of population, water, electricity, and green space were 0.17, 0.15, 0.15, and 0.03, respectively. Therefore, the first three indicators followed a cluster pattern, while the green space index was distributed in a scattered pattern throughout the city. Accordingly, the threshold population capacity, water consumption, and electricity distribution of the new city of Sahand were in the critical pressure range, while the green space index was on a favorable threshold; hence, the city had had a very good green space per capita in recent years and its tolerance capacity was more than 80%. Keywords: Urban Carrying Capacity System, Gates Ardaji Statistics, Moran Spatial Autocorrelation Analysis, New City of Sahand ReferencesAbbas Zadeh Tehrani, N. (2009). Integrating Carrying capacity's concepts into the urban planning and management process, case study: Spatial indicators of waste generation in Tehran metropolis. Journal of Environmental Sciences, 6(2), 87-104 (in Persian).Ahmadi Dehka, F., Sajjadi, Zh., & Vahedi Yeganeh, F. (2017). Measuring the feasibility of urban environmental culture on the way to sustainable urban development, case study: Sanandaj city. Journal of Sustainable City, 1(1), 1-13 (in Persian).Arghan, A., & Sha'bani, M. (2016). From the growth of the city to the sustainable urban development and the environmental dimension of the metropolis of Tehran. The Conference on Islamic and Historical Architectural and Urban Planning Research in Iran (in Persian).Asghari, A. (2013). Spatial statistics analysis with ArcGIS. Tehran: Publications of the Municipal Information and Communication Technology Organization (in Persian).Asgharpour, M. J. (2012). Multi-criteria decision making. Eleventh Edition. Tehran: Tehran University Press (in Persian).Behrad, F., Hadipour, M., Naderi, M., & Kazemi, A. (2018). Ecotourism carrying capacity evaluation with emphasis on sustainable development in Bisheh Waterfall as a geotourism area. Journal of Environmental Science and Technology, 21(10), 81-91 (in Persian).Brown, K., Turner, R. K., Hameed, H., & Bateman, I. A. N. (1997). Environmental carrying capacity and tourism development in the Maldives and Nepal. Journal of Environmental Conservation, 24(4), 316-325. https://doi.org/10.1017/S0376892997000428.Changliang, L., & Lina, L. (2012). Theoretical research of the urban comprehensive carrying capacity in the epoch of urbanization. International Journal of Financial Research, 3(1), 105-113. https://doi.org/10.5430/ijfr.v3n1p105.Chennamaneni, R., & Rao, S. (2007). Assessment of urban carrying capacity: A case study of environmental and institutional implications for water resource management in Hyderabad. Research in Agricultural & Applied Economics, 893. https://doi.org/10.22004/ag.econ.36945.Clarke, A. L. (2002). Assessing the carrying capacity of the Florida Keys. Journal of Population and Environment, 23(4), 405-418. https://doi.org/10.1023/A:1014576803251.El Ghorab, H. K., & Shalaby, H. A. (2016). Eco and green cities as new approaches for planning and developing cities in Egypt. Alexandria Engineering Journal, 55(1), 495-503. https://doi.org/10.1016/j.aej.2015.12.018.Gharakhlou, M., & Abedini, A. (2008). Evaluating the challenges and problems of new cities and their success rate in Iran: Sahand New City. Journal of Space Planning, 1, 165-191 (in Persian).Golizadeh Sarabi, Sh., & Ghaffari, E. (2013). Evaluation of the capacity of tourism in Mashhad city. The 6th National Conference on Urban Planning and Management with an emphasis on the components of the Islamic city. Mashhad (in Persian).Hui, E. C., & Lam, M. C. (2005). A study of commuting patterns of new town residents in Hong Kong. Habitat International, 29(3), 421-437. https://doi.org/10.1016/j.habitatint.2004.01.001.Irankhahi, M., Jozi, A., Farshchi, P., Shariat, M., & Liaghati, H. (2017). Combination of GISFM and TOPSIS to evaluate urban environment carrying capacity (Case study: Shemiran City, Iran). International Journal of Environmental Sciences and Technology, 5(6), 142-16. https://doi.org/10.1007/s13762-017-1243-0.Jafari, F., & DinParvar, N. (2022). Evaluation of urban carrying capacity of region 4 of Tabriz. Journal of Research and Urban Planning, 13(50), 286-301 (in Persian).Kang, P., & Xu, L. (2010). The urban ecological regulation is based on ecological carrying capacity. Procedia Environmental Sciences, 2, 1692-1700. https://doi.org/10.1016/j.proenv.2010.10.180.Kazemipour, Sh. (2013). Basics of demography. Second Edition. Tehran: Asia and Pacific Population Studies and Research Center (in Persian).Kyani Sadr, M., Mahmoudi, S., & Veisi, Z. (2019). Evaluation of the tourism board capacity of Sefidkooh Lorestan protected area. Quarterly Journal of Geography and Territorial Spatial Arrangement, 10(34), 131-146 (in Persian).Linyu, X. U., Peng, K. A. N. G., & Jinjin, W. E. I. (2010). Evaluation of urban ecological carrying capacity: A case study of Beijing, China. Procedia Environmental Sciences, 2, 1873-1880. https://doi.org/10.1016/j.proenv.2010.10.199.Liu, R. Z., & Borthwick, A. G. (2011). Measurement and assessment of the carrying capacity of the environment in Ningbo, China. Journal of Environmental Management, 92(8), 2047-2053. https://doi.org/10.1016/j.jenvman.2011.03.033.Majnounian, H. (1995). Discussions about parks, green spaces and promenades. First Edition. Tehran: Organization of Parks and Green Spaces of Tehran Municipality (in Persian).Makhfi, G., & Shaiste, K. (2018). Estimating the capacity of Hamedan urban range using pressure number model. Space Planning and Preparation, 23(4), 63-85 (in Persian).Mohammadi, R. (2013). The importance of green space in sustainable urban development. The First National Conference on Civil Engineering, Architecture and Sustainable Development. Yazd (in Persian).Mubaraki, O. (2017). Evaluation and measurement of subjective indicators of quality of life in the new city of Sahand. Journal of Population, 23(95), 123-107 (in Persian).National Center for Health Management (2018). Social development and environmental stability. Tabriz: Tabriz University of Medical Sciences, Health Services (in Persian).Navarro Jurado, E., Tejada Tejada, M., Almeida García, F., Cabello González, J., Cortés Macías, R., Delgado Peña, J., ... & Solís Becerra, F. (2012). Carrying capacity assessment for tourist destinations. Methodology for the creation of synthetic indicators applied in a coastal area. Journal of Tourism Management, 33(6), 1337-1346. https://doi.org/10.1016/j.tourman.2011.12.017.New Sahand City Development Company (2019). Master plan of the new city of Sahand. (n.p) (in Persian).PourAhmad, A., Akbarpour, M., & Sotoudeh, S. (2008). Management of urban green space in District 9 of Tehran Municipality. Journal of Human Geographical Researches, (69), 41-69 (in Persian).PourJafar, M. R., Montazer al-Hojah, M., Ranjbar, E., & Kabiri, R. (2011). Investigating the process of physical development of the new city of Sahand and determining the appropriate limits for its future development. Journal of Urban Regional Studies and Research, 4(13), 81-94 (in Persian).PourYazdi, S., & Malekian, M. (2012). Estimation of the tourism range capacity of urban parks in Qom. Applied Research Journal of Geographical Sciences, (30), 211-228 (in Persian).Rezvani, M. R. (2007). Development of rural tourism. Tehran: Tehran University Press (in Persian).Sabz Andish Payesh Consulting Engineers (2008). Comprehensive revision plan of the new city of Sahand. Tabriz: New City Construction Company (in Persian).Sabzeban, M., Bashiri Zadeh, A., Hadidi Nezhad, M., Noori, A., & Alvandi, M. (2019). Sustainable urban development with an emphasis on preserving the environmental structure. The 8th National Conference on Civil Engineering, Architecture and Urban Planning. Shirvan (in Persian).Sarafi, M. (1995). Basics of regional development planning. Tehran: Management and Planning Organization of Iran (in Persian).Schroll, H., Andersen, J., & Kjærgård, B (2012). Carrying capacity: An approach to local spatial planning in Indonesia. The Journal of Transdisciplinary Environmental Studies, 11(1), 27. https://www.proquest.comdocview/1010407587.Sharma, R. (2016). Evaluating total carrying capacity of tourism using impact indicators. Global Journal of Environmental Science and Management, 2(2), 187-196. https://doi.org/10.7508/GJESM.2016.02.009.Sheikh, A., Jafari, A., Yarali, N., & Sotoudeh, A. (2012). Estimating recreational carrying capacity of Gheisary protected area in Chaharmahal & Bakhtiari Province. Scientific Research Journal of Applied Ecology, 2(5), 51-64 (in Persian).Tabeei, M. S., Rashidi, A., & Ekhtiari Amiri, R. (2019). Convergence in the shadow of the environment: Caspian environmental issues and regional convergence. Strategic Studies of Public Policy, 10(34), 200-226 (in Persian).Taleshi, M., Rostami, Sh., Aliakbari, E., & Vejdani, H. (2018). Explaining the fundamental effective factors on land use changes with a political ecology approach; Case study: Hamedan city. Physical Development Planning, 6(2), 95-110 (in Persian).Wei, Y., Huang, C., & Xie, L. (2016). An evaluation model for urban carrying capacity: A case study of China's mega-cities. Habitat International, 53, 87-96. https://doi.org/10.1016/j.proenv.2015.07.062.Widodo, B., Lupyanto, R., Sulistiono, B., Harjito, A., Hamidin, J., Hapsari, E., … & Ellinda, C. (2015).  Analysis of environmental carrying capacity for the   development of sustainable settlement in Yogyakarta urban area. Procedia Environmental Sciences, 28, 519-527. https://doi.org/10.1016/j.proenv.2015.07.062.Zelenka, J., & Kacetl, J. (2014). The concept of carrying capacity in tourism. Amfiteatru Economic Journal, 16(36), 641-654. http://hdl.handle.net/10419/168848.